1992
DOI: 10.1051/apido:19920305
|View full text |Cite
|
Sign up to set email alerts
|

Natural mating of instrumentally inseminated queen bees

Abstract: Summary — Virgin queens homozygous for the recessive cordovan body color gene were inseminated with semen of cordovan drones. The queens were divided into 4 groups and were treated as follows: 1), inseminated with 8 mm 3 of semen; 2), treated with CO 2 before insemination with 8 mm 3 of semen; 3), inseminated twice with 4 mm 3 of semen; and 4), treated twice with CO 2 , ie before and after insemination with 8 mm 3 of semen. Queen excluders were removed from the entrances after the last treatment. Mating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 2 publications
2
10
0
Order By: Relevance
“…Only 8 queens (20%) did not lay eggs and 3 of them died while passing queen excluders and when attempting to fly, possibly to attempt natural mating (Woyke and Jasinski, 1992). The remaining dead queens were found in the nuclei, ie 2 from Groups 1 and 2, respectively, and one from Group 3.…”
Section: Methodsmentioning
confidence: 99%
“…Only 8 queens (20%) did not lay eggs and 3 of them died while passing queen excluders and when attempting to fly, possibly to attempt natural mating (Woyke and Jasinski, 1992). The remaining dead queens were found in the nuclei, ie 2 from Groups 1 and 2, respectively, and one from Group 3.…”
Section: Methodsmentioning
confidence: 99%
“…Worker bees exposed to CO 2 have reduced longevity (Austin, 1955) and change their behavior (Skowronek and Jaycox, 1974). Exposure of virgin queens to CO 2 treatments is known to inhibit queen mating flights, cause an initial weight loss and reduce or delay queen pheromone production (Harbo, 1986b;Woyke et al, 1995). Skowronek (1976) reported that two day old queens, anaesthetized with CO 2 for 10 to 30 minutes, delayed their mating flights from 9 to 25 days, compared to untreated queens which flew on the 6th day post emergence.…”
Section: Effects Of Carbon Dioxide Treatmentsmentioning
confidence: 99%
“…The inhibition of mating flights by queens inseminated at different ages, given varied CO 2 treatments was also explored by Woyke et al (1995). In a series of studies the authors demonstrated that two inseminations or two CO 2 treatments prevented mating when queens were allowed free flight.…”
Section: Effects Of Carbon Dioxide Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Virgin queens are unmated, and generally do not lay eggs, but some do (Winston, 1987). However, if virgin queens are treated with CO 2 , they activate their ovaries and lay unfertilized eggs (Mackensen, 1947;Kaftanoglu and Peng, 1982;Woyke and Jasinski, 1992), which develop into males due to the haplodiploid sex determination system of honey bees. Queens can also begin to lay drones if they run out of stored sperm (Mackensen, 1947).…”
Section: Introductionmentioning
confidence: 99%